Selective and sensitive turn-on chemosensor for Al(iii) ions applicable in living organisms: nanomolar detection in aqueous medium1. Issue 89 (27th September 2015) - Pal, Siddhartha; Sen, Buddhadeb; Mukherjee, Manjira; Patra, Mousumi; Lahiri (Ganguly), Susmita; Chattopadhyay, Pabitra
<x xml:space="preserve">Abstract</x> A new crystallographically characterized non-cytotoxic CHEF based highly sensitive Al(iii) ion selective chemosensor (L) is useful to detect the Al(iii) ions' distribution in A549 cell lines and also able to sense Al(iii) ions in tea extract.